Maintenance Rights of Wife and Children After Divorce in Islamic Family Law - Sandi Yoga Pradana; Yulies Tiena Masriani; Diana Pujiningsih; Kalijunjung Hasibuan; Indah Dwiprigitaningtias (Universitas Muhammadiyah Palu, 2025)
Divorce in Islamic family law does not automatically eliminate a husband's responsibilities toward his former wife and their children. One of the most critical and frequently disputed issues following divorce is the right to financial support, which includes maintenance for the former wife during her iddah period and ongoing support for the children. This article explores the legal standing, forms, and implementation of post-divorce maintenance rights within the framework of Islamic family law, with a particular focus on how these principles are applied in Indonesia. By employing a normative legal approach, the study examines the foundations laid out in the Qur'an and Hadith, relevant national regulations such as the Compilation of Islamic Law (KHI), and actual judicial practices in religious courts. The findings aim to provide a thorough understanding of the legal obligations related to post-divorce maintenance, emphasizing the necessity of fair treatment and legal protection for women and children. Ultimately, this article seeks to raise awareness and contribute to a more just and responsible approach to family dissolution in Islamic contexts.